The Role of Information Technology in Empowering the Creative Economy for Sustainable Tourism - Asep Sutarman; Untung Rahardja; Fitra Putri Oganda; Shofiyul Millah; Nadia Nur Azizah (Aptisi Transactions On Technopreneurship (ATT), 2023)
Â This research aimed to assess IT's role in the creative economy. Three goals were: to gauge creative economy impact on tourist satisfaction, identify its influence on satisfaction, and provide smart tourism advice. Using a quantitative approach, data was gathered from 100 Smart Tourism users. Hypotheses were tested via Partial Least Squares Regression using SmartPLS. The model proved valid and reliable. Findings showed positive creative economy impact on tourist satisfaction. Despite its insights, the research is limited by a small sample size, potentially causing generalizability and bias issues. Practical implications include advocating smart tech adoption for improved satisfaction, promoting sustainable tourism collaboration, involving communities for aligned development, and considering environmental impacts in initiatives.